Post a New Question

Math

posted by .

Solve by using the subatitution method. (Please keep fractions as they are, don't convert to decimal.)

1. y= -3x - 1
2x - 3y= -8

2. 1 + 3y= 10
5x + 2y= 6

3. 2x - 6y= -2
x= 3y - 1

4. y= 1/7x + 3
x - 7y= -4

  • Math -

    I will do #3, you try the others

    3.

    2x - 6y = -2
    x = 3y-1

    sub into the 1st:
    2(3y-1) - 6y = -2
    6y - 2 - 6y = -2
    0 = 0

    Ahhh, since the variables dropped out and we ended up with a TRUE statement, the two equations are really one and the same equation.
    (if you simplify the first, you get the second ...
    2x - 6y = -2
    divide by 2
    x - 3y = -1
    x = 3y - 1, which was the second equation )

    So any ordered pair which satisfies the 1st will obviously also satisfy the second.

    Had we ended up with a false statement, such as 3 = 0, there would have been no solution at all

  • Math -

    Hm... so, 0=0 is the only answer for #3? You don't have to do anything else? Like plugging in for the second equation or something.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question